2010 Young Investigator Award winner: Therapeutic aprotinin stimulates osteoblast proliferation but inhibits differentiation and bone matrix mineralization. - Schoenecker, J; Mignemi, N; Stutz, C; Liu, Q; Edwards, J; Lynch, C; Holt, G; Schwartz, H; Mencio, G; Hamm, H (2010)
STUDY DESIGN: Analysis of the effect of antifibrinolytics on in vitro bone formation. OBJECTIVE: As the direct effect of antifibrinolytics on bone formation is unknown, we examined whether antifibrinolytics routinely used in spine surgery, namely, aprotinin and aminocaproic acid, affect osteoblast function in vitro. SUMMARY OF BACKGROUND DATA: Antifibrinolytics are used in spine surgery to prevent intraoperative blood loss and decrease the need for transfusion. They are either delivered systemically or included as a component of most tissue sealants. Although the role of the fibrinolytic system in wound healing is well established, reports of indirect effects on normal bone biology are emerging. This suggests that the pharmacological targeting of this system may also influence skeletal mass and integrity. METHODS: Osteoblast progenitor cells were cultured with therapeutic doses of aprotinin and aminocaproic acid. The effect of the antifibrinolytics on osteoblast development was determined by measuring cellular viability and proliferation, quantification of matrix mineralization, and genetic analysis of osteoblast differentiation markers. Protease inhibition profiles of the antifibrinolytics were determined by amidolytic chromogenic assays. RESULTS: Therapeutic concentrations of aprotinin dose-dependently inhibited plasmin's proteolytic activity, stimulated osteoblast proliferation, and inhibited osteoblast differentiation and matrix mineralization. Aprotinin inhibition of osteoblast differentiation and matrix mineralization could be recovered by removing aprotinin from culture or stimulating cells with bone morphogenetic protein-2 or plasmin. Conversely, aminocaproic acid inhibited plasmin's proteolytic activity significantly less than aprotinin and had no effect on osteoblast proliferation, differentiation, or matrix mineralization in its therapeutic range. CONCLUSION: These findings demonstrate that the antifibrinolytics have drastically different effects on osteoblasts due in part to different efficacies of protease inhibition. Further, this work suggests that the fibrinolytic proteases and their inhibitors have great potential to regulate bone by affecting the processes that control osteoblast growth and differentiation.